2010
DOI: 10.1007/s10955-010-0020-y
|View full text |Cite
|
Sign up to set email alerts
|

The Replica Symmetric Approximation of the Analogical Neural Network

Abstract: In this paper we continue our investigation of the analogical neural network, by introducing and studying its replica symmetric approximation in the absence of external fields. Bridging the neural network to a bipartite spin-glass, we introduce and apply a new interpolation scheme to its free energy, that naturally extends the interpolation via cavity fields or stochastic perturbations from the usual spin glass case to these models. While our methods allow the formulation of a fully broken replica symmetry sch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
123
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 58 publications
(126 citation statements)
references
References 15 publications
3
123
0
Order By: Relevance
“…From a theoretical physics perspective, a network of interacting B-and T-cells resembles a bi-partite spin glass. It was recently shown that such a bi-partite spin-glass is thermodynamically equivalent to a Hopfield-like neural network with effective Hebbian interactions [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…From a theoretical physics perspective, a network of interacting B-and T-cells resembles a bi-partite spin glass. It was recently shown that such a bi-partite spin-glass is thermodynamically equivalent to a Hopfield-like neural network with effective Hebbian interactions [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we consider the equivalence between the Hopfield model and a class of Boltzmann machines (Bengio, 2009) developed in Barra, Bernacchia, Santucci, and Contucci (2012) and Barra, Guerra, and Genovese (2010) and we show that this equivalence is rather robust and can be established also for the correlated and diluted Hopfield studied here. Interestingly, this approach allows the investigation of dynamic properties of the model which are as well discussed.…”
Section: Introductionmentioning
confidence: 76%
“…We conjecture this is a consequence of the choice of the decomposition (2.3). Finally, with the aim of promoting cross-fertilization among the two disciplines of Machine Learning and Disordered Statistical Mechanics, we collected the outlined results by using two among the most used methods to deal with spin-glasses, namely the replica trick [19] and the interpolation method [12], discussing both of them in great detail.…”
Section: Discussionmentioning
confidence: 99%